A longitudinal study of occlusal caries among schoolchildren in Dar es Salaam, Tanzania - Rugarabamu PGN, Poulsen S, Masalu JRP. (Blackwell Synergy, 2002)
To describe the clinical caries status and the radiographic progression of occlusal caries lesions in permanent first and second molars among primary schoolchildren in Dar es Salaam over a 3-year period. Methods: Clinical and radiographic diagnosis of caries in first and second permanent molars in 223 children aged 8–16 years were carried out annually from 1994 to 1997.